Sjögren's Syndrome: Epidemiology, Classification Criteria, Molecular Pathogenesis, Diagnosis, and Treatment - Ying Hu; Bin Wen; Yunfei Zhang; Xiaocui Wang; Xuemei Duan; Haonan Li; Yufeng Fan; Huifeng Shang; Yukai Jing (MedComm, 2025)
ABSTRACT Sjögren's syndrome (SS) is a chronic autoimmune disorder characterized by T‐cell‐mediated B‐cell hyperactivity and cytokine production, clinically manifesting, dry mouth and eyes, accompanied by pain and fatigue. The disease may progress from asymptomatic glandular involvement to systemic manifestations or even lymphoma. The pathogenesis of SS is intricate, involving a multifaceted interplay of genetic, environmental, and immunological factors. There is still uncertainty regarding the effectiveness of SS‐targeted treatments, due to the significant diversity in disease phenotypes and potentially varying responses to immunomodulatory therapies, stringent enrollment criteria and adoption of outcome metrics in clinical trials may partially explain the failure of many trials to achieve their primary outcomes. Despite the current lack of effective treatments, recent advancements have been made in epidemiology, the development of classification criteria, and the establishment of systems for assessing disease activity. Notably, enhanced insights into the pathogenesis have paved the way for the potential development of targeted therapies. This review aims to systematically synthesize the latest research advancements in the epidemiological characteristics, diagnostic criteria, molecular mechanisms, and clinical manifestations of SS, thereby providing a scientific foundation for the development of future therapeutic strategies.